Massive Mortality of a Planktivorous Seabird in Response to a Marine Heatwave. Issue 7 (2nd April 2018) - Jones, Timothy; Parrish, Julia K.; Peterson, William T.; Bjorkstedt, Eric P.; Bond, Nicholas A.; Ballance, Lisa T.; Bowes, Victoria; Hipfner, J. Mark; Burgess, Hillary K.; Dolliver, Jane E.; Lindquist, Kirsten; Lindsey, Jacqueline; et al.
Abstract: Climate change has exacerbated the occurrence of large‐scale sea surface temperature anomalies, or marine heatwaves (MHWs)—extreme phenomena often associated with mass mortality events of marine organisms. Using a combination of citizen science and federal data sets, we investigated the causal mechanisms of the 2014/2015 die‐off of Cassin's Auklets ( Ptychoramphus aleuticus ), a small zooplanktivorous seabird, during the NE Pacific MHW of 2013–2015. Carcass deposition followed an effective reduction in the energy content of mesozooplankton, coincident with the loss of cold‐water foraging habitat caused by the intrusion of the NE Pacific MHW into the nearshore environment. Models examining interannual variability in effort‐controlled carcass abundance (2001–2014) identified the biomass of lipid‐poor zooplankton as the dominant predictor of increased carcass abundance. In 2014, Cassin's Auklets dispersing from colonies in British Columbia likely congregated into a nearshore band of cooler upwelled water and ultimately died from starvation following the shift in zooplankton composition associated with onshore transport of the NE Pacific MHW. For Cassin's Auklets, already in decline due to ocean warming, large‐scale and persistent MHWs might represent a global population precipice. Plain Language Summary: During the winter of 2014/2015, thousands of Cassin's Auklets, a small seabird that breeds in the NE Pacific, were found dead on beaches from California to British Columbia, Canada. We show that wide‐scale starvation was due to a change in food quality associated with warmer ocean temperatures preceding and during the die‐off. This research highlights that more frequent and intense ocean warming events may have complex impacts on food webs with population consequences for marine predators, particularly seabirds such as Cassin's Auklets. Key Points: During the winter of 2014/2015, over 9, 000 (>100 x normal) dead Cassin's Auklets were observed on beaches from California to British Columbia The die‐off was ultimately caused by a reduction in zooplankton prey energy content as a result of the NE Pacific marine heatwave (MHW) The NE Pacific MHW likely inflated event magnitude by compressing cold‐water habitat, and by proxy live birds, closer to shore than usual